THE REGION OF CENTRAL ASIA - Oxunjanov Abdulhay Fozil o’g’li (Journal Park Publishing, 2025)
This article explores the historical and intellectual significance of Nasaf (Nakhshab), a city in Central Asia (modern-day Uzbekistan), as a major center of Islamic scholarship. It provides an overview of the region's deep connection to Islamic culture since the 7th century CE and contrasts the sedentary lifestyle of its people with the nomadic cultures of neighboring regions. The main body of the text offers concise biographies of several influential scholars who emerged from Nasaf, including Abu al-Barakat al-Nasafi and Umar ibn Muhammad Abu Hafs al-Nasafi. The article highlights their key contributions to Islamic jurisprudence (fiqh), Quranic exegesis (tafsir), and hadith, underscoring Nasaf's lasting legacy as a source of invaluable intellectual and spiritual heritage for the Muslim world.
Keywords: Nasaf (or Nakhshab), islamic Scholars, Central Asia, Islamic Jurisprudence (Fiqh), Quranic Exegesis (Tafsir), Hanafi Madhhab.